The Association of Sedentary Behaviour and Cognitive Function in People Without Dementia: A Coordinated Analysis Across Five Cohort Studies from COSMIC - Maasakkers, Carlijn M. (Sports Med, 2019)
BACKGROUND: Besides physical activity as a target for dementia prevention, sedentary behaviour is hypothesized to be a potential target in its own right. The rising number of persons with dementia and lack of any effective treatment highlight the urgency to better understand these modifiable risk factors. Therefore, we aimed to investigate whether higher levels of sedentary behaviour are associated with reduced global cognitive functioning and slower cognitive decline in older persons without dementia. METHODS: We used five population cohorts from Greece, Australia, USA, Japan, and Singapore (HELIAD, PATH, SALSA, SGS, and SLAS2) from the Cohort Studies of Memory in an International Consortium. In a coordinated analysis, we assessed the relationship between sedentary behaviour and global cognitive function with the use of linear mixed growth model analysis (mean follow-up range of 2.0–8.1 years). RESULTS: Baseline datasets combined 10,450 older adults without dementia with a mean age range between cohorts of 66.7–75.1 years. After adjusting for multiple covariates, no cross-sectional association between sedentary behaviour and cognition was found in four studies. One association was detected where more sedentary behaviour was cross-sectionally linked to higher cognition levels (SLAS2, B = 0.118 (0.075; 0.160), P < 0.001). Longitudinally, there were no associations between baseline sedentary behaviour and cognitive decline (P > 0.05). CONCLUSIONS: Overall, these results do not suggest an association between total sedentary time and lower global cognition in older persons without dementia at baseline or over time. We hypothesize that specific types of sedentary behaviour may differentially influence cognition which should be investigated further. For now, it is, however, too early to establish undifferentiated sedentary time as a potential effective target for minimizing cognitive decline in older adults without dementia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40279-019-01186-7) contains supplementary material, which is available to authorized users.